2008
DOI: 10.3174/ajnr.a0963
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumor Imaging in Clinical Trials

Abstract: SUMMARY:There are substantial challenges in the radiologic evaluation of tumor size during clinical trials, and it is important for neuroradiologists to have a firm understanding of these issues. This review will examine measurement approaches, response criteria, selection of lesions for measurement, technical imaging considerations, interval between tumor measurements and response confirmation, and validity of imaging as a measure of efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
108
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 18 publications
(31 reference statements)
0
108
1
4
Order By: Relevance
“…Volumetric standards were established by using an extrapolation from the MacDonald criteria by converting orthogonal measurements to a volume assuming a spheric lesion (Table 1). 10 "Complete response" was defined as complete absence of contrast-enhancing tumor for all techniques. "Partial response" was defined as Ͼ30% decrease in the sum of maximal diameters for 1D, Ͼ50% decrease in the product of orthogonal diameters for 2D, and Ͼ65% in volume for volumetric techniques.…”
Section: Definition Of Responsementioning
confidence: 99%
See 3 more Smart Citations
“…Volumetric standards were established by using an extrapolation from the MacDonald criteria by converting orthogonal measurements to a volume assuming a spheric lesion (Table 1). 10 "Complete response" was defined as complete absence of contrast-enhancing tumor for all techniques. "Partial response" was defined as Ͼ30% decrease in the sum of maximal diameters for 1D, Ͼ50% decrease in the product of orthogonal diameters for 2D, and Ͼ65% in volume for volumetric techniques.…”
Section: Definition Of Responsementioning
confidence: 99%
“…12,13 Despite the potential advantages of volumetric assessment, this technique requires manual outlining of the contrast-enhancing border, which can be both time-consuming and technically challenging. 5,10 This technique may be further limited in cases with irregular enhancement and subependymal extension. 10 For these reasons, computer-aided volumetry techniques applied to the contrast-enhancing tissue represent a potential tool to aid the radiologist in following these patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The most important reason may be that the residual lesions after resection were characterized by cavities and irregular shapes, and the 2-dimensional measurement per RANO criteria cannot reflect the real response of GBM after CCRT. Several studies (24)(25)(26) have shown that volumetric measurement is superior to 2-dimensional measurement in evaluating the radiographic response of GBM. Wen et al (27) believed that the use of volumetric assessment would allow for more accurate determination of the contrast-enhancing and nonenhancing volumes and overcome the limitations of 2-dimensional measurements of lesions surrounding a surgical cavity.…”
Section: Discussionmentioning
confidence: 99%